Adaptive control through on-line optimization. The MPCI paradigm and variants - Nikolaou, Michael; Eker, S. Alper (Zielona Góra: Uniwersytet Zielonogórski)
A new variant of Model Predictive Control and Identification (MPCI) is proposed. The on-line objective is not to minimize the sum of square errors, but to maximize on-line the sum of the lower bounds on the minimum eigenvalues of the information matrices over finite horizons.
Keywords: adaptive control; model predictive control; closed-loop identification; persistent excitation; linear matrix inequalities; semidefinite programming